Staphylococcus aureus Toxins - Schwan, William (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Staphylococcus aureus is a common inhabitant of the human body with which we co-exist. However, this species can also cause disease in humans when an appropriate opportunity arises, such as a cut or some other breakdown in our body's defenses. S. aureus is able to initiate infections due, in part, to the diverse group of toxins that they secrete. The exotoxins produced by S. aureus can cause direct damage, thwart our own body's defenses, or trigger massive amounts of cytokines that lead to indirect damage within the human body. In this book are 12 research articles that deal with different aspects of staphylococcal exotoxins. Some of the work gives an overview about how the toxins contribute to the disease process. Other articles discuss different aspects of several exotoxins, and two articles are centered on countermeasures against S. aureus infections. Overall, this book will give the reader a good overview of how staphylococcal exotoxins contribute to initiating and sustaining infections in humans.